The halos and environments of nearby galaxies (HERON) survey: IV. complexity in the boxy galaxies NGC 720 and NGC 2768 - Koch-Hansen, Andreas; Pasquali, Anna; Rich, R. Michael; Gerhard, Ortwin; Müller, Oliver (Astronomy and astrophysics, 2024)
The shapes of galaxies, their outer regions in particular, are important guideposts to their formation and evolution. In this work, we report on the discovery of strongly box-shaped morphologies of the otherwise well-studied elliptical and lenticular galaxies NGC 720 and NGC 2768 from deep imaging. The boxiness is strongly manifested in the parameter shape A4/a of −0.04 in both objects, and significant center shifts of the isophotes of ∼2–4 kpc are also seen. One reason for such asymmetries commonly stated in the literature is a merger origin, although the number of such cases is still sparse, and the exact properties of the individual boxy objects are highly diverse. Indeed, for NGC 2768, we identify a progenitor candidate (dubbed “Pelops”) in the residual images, which appears to be a dwarf satellite that is currently merging with NGC 2768. At its absolute magnitude of Mr of −12.2 mag, the corresponding Sersic radius of 2.4 kpc is more extended than those of typical dwarf galaxies from the literature. However, systematically larger radii are known to occur in systems that are in tidal disruption. This finding is bolstered by the presence of a tentative tidal stream feature on archival GALEX data. Finally, further structures in the fascinating host galaxy include rich dust lanes and a vestigial X-shaped bulge component.
Online veröffentlicht: 6. Februar 2024
Gesehen am 31.07.2024